Meniscus‐Targeted Injections for Chronic Knee Pain Due to Meniscal Tears or Degenerative Fraying: A Retrospective Study. (18th March 2019) - Wilderman, Igor; Berkovich, Rachel; Meaney, Christopher; Kleiner, Omer; Perelman, Vsevolod
Abstract : Objectives: Meniscal tears caused by acute trauma or degenerative fraying affect a wide array of individuals. An effective, long‐lasting treatment has widely been sought after. Intra‐articular corticosteroid injections have been among the methods of controlling pain for more than 60 years. However, such injections tend to produce short‐lasting results, with profound effects lasting an average of up to 4 weeks. The purpose of this study was to determine the average duration and magnitude of pain relief after meniscal‐targeted injections. Methods: The electronic medical records of 135 patients were accessed for this retrospective chart review. Patients who had meniscal tears or degenerative fraying and were treated with meniscal‐targeted injections were selected. Patients' visual analog scale (VAS) pain scores (before and after treatment) were recorded, along with the percentage of pain relief and duration of pain relief. Results: Ultrasound‐guided meniscus‐targeted corticosteroid injections for meniscal tears or degenerative fraying produced 5.68 (SD, 5.28) weeks of pain relief on average, with a decrease in pain from initial to follow‐up visits of 2.14 ( P < .0001) as per the visual analog scale score, and an Integral of Pain Relief score of 3.98. Conclusions: Our findings indicate a substantial benefit from 20‐ or 40‐mg meniscus‐targeted triamcinolone injections, granted the limitations of chart review research and no control group comparison. Results highlight the need for future prospective research comparing meniscus‐targeted injections with intra‐articular injections to identify a better modality for treating patients with chronic knee pain caused by meniscal tears or degenerative fraying.